Research Integrity and Research Fairness: Harmonious or in Conflict? - Labib, Krishma (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
Dominant initiatives focusing on research integrity are changing the research landscape by leading to the development and application of rules, guidelines and standards that researchers across borders have to abide by. There is an increasing attention within these initiatives to the importance of research fairness for conducting responsible research. However, some stakeholders view research fairness as separate and sometimes even conflicting with research integrity. To make sense of these accounts, I explore the relationship between research integrity and research fairness. I argue that dominant research integrity initiatives are currently at odds with research fairness. This is because these initiatives largely ignore anticolonial views about research and thereby perpetuate coloniality in research. Furthermore, dominant initiatives only engage superficially with aspects of fairness that are least controversial and current. Moreover, these research integrity initiatives impose Eurocentric ideals about responsible research to other countries, thereby contributing to “ethical imperialism”. Considering the wide reach of dominant research integrity initiatives and their influence on research, it is therefore urgent to develop an anticolonial research integrity agenda that takes fairness seriously.